A High Content Screening Assay for Evaluation of Biomaterial‐Mediated Cell Fusion Processes. Issue 1 (December 2014) - Rijckaert, Bart; Neffe, Axel T.; Roch, Toralf; Gebauer, Tim; Pierce, Benjamin F.; Görs, Julia; Smink, Jeske J.; Gossen, Manfred; Lendlein, Andreas; Leutz, Achim; Lendlein, Andreas; Domb, Abraham J.
Summary Biomaterials are of increasing importance in regenerative medicine and entail delivery systems in somatic cell therapies, matrices for tissue engineering or tissue regeneration. The evaluation of biomaterial induced biological effects remains a key issue in clinical application. Cell‐based assays for potential cytotoxic and immunological responses have been developed but are often inadequate to address cell‐type specific responses to biomaterials. To quantitatively monitor attachment, survival, proliferation and fusion‐controlled differentiation of osteoclasts (bone resorbing cells), a High Content Screening (HCS) assay has been developed based on osteoclast differentiation of the murine monocytic cell line RAW 264.7. This assay was applied to investigate the influence of degradation products of polymers from gelatin and lysine diisocyanate, which display tailorable mechanical properties and have potential as biomaterials. The data show that the degradation products inhibit formation of multinuclear osteoclasts and suggest a potential support of bone regeneration by suppression of bone resorption.